Healthcare affordability in Singapore. - Goh, Pei Shan. (2008)
In 2000, Singapore’s healthcare system was ranked 6th out of 191 countries in WHO’s World Health Report on health systems. While there has been a general agreement on the cost effectiveness of the system, the same could not be said of affordability. This paper attempts to investigate the affordability of healthcare in Singapore by estimating the cost of treatment for heart attack in Singapore and comparing it with a representative household’s available sources of financing the treatment- discretionary savings and 3Ms. Our results show that healthcare in Singapore is indeed unaffordable for the typical household and the reason for the unaffordability can be attributed to (1) the middle income squeeze and (2) elderly dependence on the household.